Efektivitas Instalasi Pengolahan Air Limbah Berdasarkan Parameter COD, BOD, TSS, pH (Studi Kasus Industri Tahu di Dusun Janten Ngestiharjo Kasihan Bantul) - Setiadji, Wawan; Effendi, Novan Rico; Sutrisno, Widarto; Mashadi, Ahmad; Galuh, Dimas Langga Chandra (Proceedings Series on Physical & Formal Sciences, 2023)
The liquid waste generated from tofu production process contains high Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD), Total Suspended Solid (TSS) as well as low pH levels or acidity. Therefore, the tofu waste needs to be treated before being discharged into the environment to prevent negative impacts on the surrounding environment. Thus, this study aimed to test the effectiveness of the tofu wastewater treatment plant by monitoring the parameters of COD, BOD, TSS and pH using the closed reflux titrimetry, gravimetri and pH meter methods. The sampling was carried out with triple sampling (triplo) at each testing point, which were the equalization tank, anaerobic baffle reactor tank, anaerobic filter tank, and final settling tank. The sample testing was conducted at the "Balai Laboratorium Kesehatan dan Kalibrasi Yogyakarta". The results of the testing were used to determine the reduction in COD and the increase in pH between the wastewater treatment plant tanks, and then the effluent of the wastewater treatment plant was compared with the wastewater quality standards. The results of this study indicate that the average reduction of COD in the effluent is 94%, BOD is 93%, and TSS is 87%. Based on these findings, it can be concluded that the effluent from the wastewater treatment plant is not yet effective in meeting the wastewater quality standards. However, it is worth noting that the pH parameter meets the wastewater quality standards, with an increase of +1.38 compared to the influent pH level. Therefore, in terms of this parameter, the wastewater treatment plant can be considered effective in raising the pH.